Molecular mechanism of parallel fiber-Purkinje cell synapse formation - Mishina, Masayoshi; Uemura, Takeshi; Yasumura, Misato; Yoshida, Tomoyuki (Frontiers in Neural Circuits, 2012)
The cerebellum receives two excitatory afferents, the climbing fiber (CF) and the mossy fiber-parallel fiber (PF) pathway, both converging onto Purkinje cells (PCs) that are the sole neurons sending outputs from the cerebellar cortex. Glutamate receptor δ2 (GluRδ2) is expressed selectively in cerebellar PCs and localized exclusively at the PF-PC synapses. We found that a significant number of PC spines lack synaptic contacts with PF terminals and some of residual PF-PC synapses show mismatching between pre- and postsynaptic specializations in conventional and conditional GluRδ2 knockout mice. Studies with mutant mice revealed that in addition to PF-PC synapse formation, GluRδ2 is essential for synaptic plasticity, motor learning, and the restriction of CF territory. GluRδ2 regulates synapse formation through the amino-terminal domain, while the control of synaptic plasticity, motor learning, and CF territory is mediated through the carboxyl-terminal domain. Thus, GluRδ2 is the molecule that bridges synapse formation and motor learning. We found that the trans-synaptic interaction of postsynaptic GluRδ2 and presynaptic neurexins (NRXNs) through cerebellin 1 (Cbln1) mediates PF-PC synapse formation. The synaptogenic triad is composed of one molecule of tetrameric GluRδ2, two molecules of hexameric Cbln1 and four molecules of monomeric NRXN. Thus, GluRδ2 triggers synapse formation by clustering four NRXNs. These findings provide a molecular insight into the mechanism of synapse formation in the brain.